Pelatihan Cerdas Penggunaan Media Sosial Bagi Remaja Di Desa Penembang - Alfatah, Dhika; Ramadhan, Hanung wahyu; Juliansyah, Febri; Sirait, Roi Sunjaya; Akbar, Bobby Adi (Jurnal Kewirausahaan dan Bisnis, 2022)
Nowadays, the use of technology is very fast and massive, and today's technology users do not look at age and gender status with easy use Digital is a form of modernization where everything can be done through this sophisticated equipment to facilitate people's affairs. this is what encourages a person's perspective in living an increasingly sophisticated life today.The purpose of writing an article is to provide training related to the use of social media for adolescents in Penembang Village. So that they are proficient with technology and digital literacy.